2016
DOI: 10.1093/dnares/dsv040
|View full text |Cite
|
Sign up to set email alerts
|

Identification, cloning and characterization of R2R3-MYB gene family in canola (Brassica napusL.) identify a novel member modulating ROS accumulation and hypersensitive-like cell death

Abstract: The R2R3-MYB proteins comprise one of the largest families of transcription factors in plants. Although genome-wide analysis of this family has been carried out in some plant species, little is known about R2R3-MYB genes in canola (Brassica napus L.). In this study, we have identified 76 R2R3-MYB genes in the canola genome through mining of expressed sequence tags (ESTs). The cDNA sequences of 44 MYB genes were successfully cloned. The transcriptional activities of BnaMYB proteins encoded by these genes were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…CATs acted downstream of both MYB78 and MYB15, which regulate reactive oxygen species (ROS)-dependent cell death in AZ separation825. Two CAT genes were confirmed to express in abscissions in both ethylene and water-deficit stress treatments (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…CATs acted downstream of both MYB78 and MYB15, which regulate reactive oxygen species (ROS)-dependent cell death in AZ separation825. Two CAT genes were confirmed to express in abscissions in both ethylene and water-deficit stress treatments (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…The term ‘hypersensitive‐like cell death’ or similar is often used simply when cell death is observed without any explicit link to R ‐genes, the defence response or disease resistance (e.g. Chen et al , ; Király et al , ; Kumar and Kirti, ; Na et al , ; Wei et al , ).…”
Section: Conceptsmentioning
confidence: 99%
“…The term 'hypersensitive-like cell death' or similar is often used simply when cell death is observed without any explicit link to R-genes, the defence response or disease resistance (e.g. Chen et al, 2016;Király et al, 2008;Kumar and Kirti, 2015;Na et al, 2015;Wei et al, 2016). This review will take a rather narrow view of HR, confined to the localized rapid cell death and excluding the other associated responses induced by the activation of NLR proteins.…”
Section: How Should Hr Be Defined?mentioning
confidence: 99%
“…Zhou et al [ 8 ] identified 247 BnbZIPs in B. napus and performed detailed structural analyses. Chen et al [ 33 ] identified 76 R2R3 MYBs in the B. napus genome through excavating expressed sequence tags (ESTs), and the transcript abundance level analysis during abiotic conditions and ABA treatment identified a group of MYBs that responded to one or more treatments. Recently, Hajiebrahimi et al [ 34 ] identified 249 R2R3 MYBs in B. napus , and the authors reported that these genes were highly expressed in the roots under high salinity treatment after 24 h. Three MYB genes, BnaMYB21, BnaMYB141, and BnaMYB148 have been suggested improve salt-tolerance in B. napus .…”
Section: Introductionmentioning
confidence: 99%